Morphology of the walls of the cavernous sinus of Cebus apella (tufted capuchin monkey) - Domingues, Robson José de Sousa; Muniz, José Augusto P. Carneiro; Tamega, Oisenyl José [UNESP] (FapUNIFESP (SciELO), 1999)
The morphology of the dura mater and its relationship with the structures of the cavernous sinus were analyzed in five tufted capuchin monkeys (Cebus apella) using histological sections, showing that the walls of the cavernous sinus of this species are similar to those of other primates, including man. Except for the medial wall of the cavernous sinus, the remaining walls consist of two distinct dura mater layers. The deep layer of the lateral wall of the cavernous sinus is contiguous to the sheath of the oculomotor, trochlear and ophthalmic nerves. Arterioles, venules, venous spaces, neuronal bodies and nervous fiber bundles are found on this lateral wall.
Keywords: Cavernous sinus; Cebus apella; Cranial nerves; Dura mater; Primates